Managing Customer Relationships in Service Organizations - Adhikari, Balaram; Adhikari, Bibhav (Administration and Management Review, 2010)
Presently, many managers regard Customer Relationship Management (CRM) as a database application or software solution and try to adopt it to become an agile company. But CRM has extended its scope beyond that. In real terms, CRM is a philosophy and the software solution part is just a tool to aid better implementation of the philosophy. CRM has existed since ages. Either it is the corner betel shop owner who recognizes regular customers and offers them his regular betel or a technologically advanced Call Center's executive who addresses customers by their names when he makes a call by looking up in their database for the customer's detail. This paper tries to understand this philosophy and its uses in the high customer blends open to service sectors and also tries to find the uses of a CRM to improve the customer satisfaction levels and develop a better CRM framework. Key Words: Service; Organisation; Managing Customer; Relationship Administration and Management Review Volume 21, No. 2, 2009 Page: 64-78